Guarantees in construction contracts - Kadhem Hussein al-Rubaie (Journal of Madenat Alelem University College, 2015)
Show us that the Contracting arose originally in the arms of the civil law, but due to the development of economic and social conditions have added to the Contracting Terms unusual in civil contract and a guarantee to the public interest as the subject of entrepreneurship is one of the projects or buildings of government departments, for this and put in the contract terms of insurance, fines and pull contract from one party is the government in addition to insurance, execution and style tenders. The ratios of the methods of the tenders were not government regulations no. (1) For the year 2014 its share in most of them and encourage and even legitimize the financial and administrative corruption as always prefer to choose the contractor, according to the will of the circle. The insurance and fines conclusion they are few and is a deterrent to the contractor and the best of them for the public benefit is a penalty clause which up to 70% of the contract amount. Also suggested activating the law of graft No. 15 for the year 1958 for all financial and administrative corruption titled where did you get this? Add file to give each contractor to the Commission on Security and integrity to follow the spoilers from the beginning and to the end. Pena also unnecessary to activate the law of government debt collection No. 56 of 1956 which has become disabled and give the Director-General of the Department of the validity of the port each year in order to get government debt, the most convenient and easiest way instead of the courts, which is time consuming. Pena also unnecessary to refer the dispute to arbitration courts first second and not left to the desire of the contractor willing to preferred arbitration courts first and later because the disruption of the public facility to the state.